A narrative review on the applications of intracavitary contrast-enhanced ultrasonography in pediatric lower genitourinary anomalies - Ren, Jiayu; Ma, Ting; Huang, Shuyan; Chen, Gongquan; Dietrich, Christoph F.; Peng, Yuexiang; Cui, Xinwu (Frontiers in Pediatrics, 2023)
Purpose We mainly aimed to perform a narrative review of clinical applications of three intracavitary contrast-enhanced ultrasonography (CEUS) including contrast-enhanced voiding urosonography (ceVUS), contrast-enhanced retrograde urethrosonography (ceRUG), contrast-enhanced genitosonography (ceGS) in pediatric lower genitourinary anomalies. Method A literature search of PubMed and Web of Science databases was conducted as of July 1, 2022 on all studies published in English using the search terms ‘contrast-enhanced voiding urosonography’, ‘contrast-enhanced retrograde urethrosonography’, and ‘contrast-enhanced genitosonography’. Trials were limited to pediatric subjects (ages ≤18 years) with no time restrictions. The inclusion criteria were studies on ceVUS, ceRUG, and ceGS to evaluate pediatric lower genitourinary anomalies. Two independent authors summarized the included articles. Results Finally, a total of 48 original articles and 6 case reports or case series were included, of which 50 (93%) were only relevant to ceVUS, 3 (5%) articles involved ceGS, while only one (2%) article involved ceRUG and 87% of the applications of ceVUS were focused on vesicoureteral reflux (VUR). We also searched 24 related reviews, of which 20 involved ceVUS in diagnosing VUR, and 4 involved ceRUG and ceGS for other lower genitourinary anomalies. Conclusion Intracavitary CEUS including ceVUS, ceRUG, and ceGS in pediatrics has many advantages over other radiological examinations in diagnosing lower genitourinary anomalies. Although ceVUS is widely used in detecting VUR, ceRUG and ceGS for evaluating the urethral pathologies and urogenital sinus have also become promising techniques.